Optimizing Religious Learning in Public Schools: Challenges and Solutions to Time Limitations - Asqolani, Najwa; Fihris, Fihris; Raihan, Muhammad Juhan (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
Religious education in public schools plays an important role in shaping the spiritual, ethical, and moral character of students, but its implementation faces a number of complex obstacles. This study aims to identify various challenges in religious education in public schools, particularly time constraints, and to offer relevant solutions to optimize its implementation. The research method used is a literature study by reviewing literature from national journals, proceedings, and scientific books over the last ten years to obtain a comprehensive picture of this issue. The results of the analysis show that time constraints are a major factor affecting the depth of students' understanding of religious values, as limited class hours often make the learning process formal and fail to touch on affective and applicative aspects. Other significant challenges include low student interest and motivation to learn, limited digital learning facilities that can support creativity, and limited teacher competence in developing innovative contextual methods. In addition, the multicultural factor in the form of diversity in students' cultural and religious backgrounds requires a high level of sensitivity so that religious education remains inclusive and harmonious. The conclusion findings of this study demonstrate that enhancing the quality of religious education necessitates a multifaceted approach that extends beyond mere augmentation of instructional hours. Achieving this objective necessitates a multifaceted approach, encompassing comprehensive support from various stakeholders, including teachers, schools, families, and policymakers